Marmaduke Pickthall: Islam and the Modern World - Nash, Geoffrey P. (03d19de9-3e9e-4cf4-804c-bf03b446bbdc, 2016)
Marmaduke Pickthall: Islam and the Modern World makes an important contribution to the field of Muslims in Europe in the first half of the twentieth century. This volume of essays marks eighty years since the death of Marmaduke Pickthall. Readership: All interested in the history of Islam in Britain and the colonial world, British Muslim fiction, travel writing, and English translations of the Qurʾan.